2017
DOI: 10.1139/cjc-2017-0219
|View full text |Cite
|
Sign up to set email alerts
|

Improved carbon dioxide storage over clay-supported perhydroxylated glucodendrimer

Abstract: Low-cost biosourced hybrid microporous adsorbents with improved affinity towards carbon dioxyde (CO2) were prepared through the incorporation of various amounts of glucosylated dendrimer into bentonite- and montmorillonite-rich composite materials. Characterization by nitrogen adsorption–desorption isotherms, surface specific and pore size analyses (BET and BJH), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) revealed changes in the interlayer spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The intensity increase in the stretching vibration band of the free OH groups around 3604 cm −1 provides clear evidence of the incorporation of increasing number of OH groups in the clay structure [34]. The shift of this band towards 3654 cm −1 indicates that at least a part of the OH groups of EPS are involved in interactions with the inorganic support and water molecules [35]. The bands observed at 1220 and 1042 cm −1 were attributed to the asymmetric stretching of the siloxy group.…”
Section: Eps Interactions With Namtmentioning
confidence: 93%
“…The intensity increase in the stretching vibration band of the free OH groups around 3604 cm −1 provides clear evidence of the incorporation of increasing number of OH groups in the clay structure [34]. The shift of this band towards 3654 cm −1 indicates that at least a part of the OH groups of EPS are involved in interactions with the inorganic support and water molecules [35]. The bands observed at 1220 and 1042 cm −1 were attributed to the asymmetric stretching of the siloxy group.…”
Section: Eps Interactions With Namtmentioning
confidence: 93%
“…Nousir et al [141] modified bentonite and montmorillonite clay with perhydroxylated glucodendrimenr for CO 2 adsorption and CRC data revealed that CO 2 adsorption involves physical adsorption with the OH of the dendrimer. In the same year, Shah et al [27] conducted a study of the adsorption of CO 2 and NH 3 gas regarding cationic clay and anionic clay.…”
Section: Air Pollutionmentioning
confidence: 99%
“…The basic strength accounts for CO 2 retention strength, and is proportional to the CO 2 desorption temperature. 30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] For this purpose, 45-50 mg of each material sample was prone to previous saturation with dry and O 2 -free CO 2 and then to a 5 C min À1 heating rate from 20 C to a given temperature threshold under 5 mL min À1 nitrogen stream. This temperature threshold was evaluated as the stability range through TGA by means of a TA Instruments TGA (Q500)/discovery MS equipment.…”
Section: Materials Characterizationmentioning
confidence: 99%